ETHICS AND THE NIGERIAN PUBLIC SERVICE: A STUDY OF IMO STATE CIVIL SERVICE - Ihemadu, Michael Chinazam (African Journal of Social and Behavioural Sciences, 2020)
This work concentrates principally on Ethics and the Nigerian Public Service with the Imo State Civil Service as a case study. It critically examines the level of work ethics among Imo State Civil Servants in the discharge of their official functions. In addition, the study carefully looks at the effects of work ethics on the performance and productivity of civil servants. This paper essentially made use of secondary source of data which were analysed descriptively. It adopted the systems approach as our framework of analysis our choice of systems model is hinged on our belief that organization like Civil Service cannot survive without interactions with its environment and this approach provides a good explanation of the essence of this interaction. The major outcome of this wor among other things has in the contribution it will make towards the development an practice of administrative responsibility. The scope of this study covers the period between 2011 and 2019. Finally, it X-rays the measures that could be taken to ameliorate the work ethics and performance/productivity of the workers.